Something new under the sun : a novel - Kleeman, Alexandra (Hogarth, 2021)
"East-coast novelist Patrick Hamlin has come to Hollywood with simple goals in mind: overseeing the production of a film adaptation of one of his books, preventing starlet Cassidy Carter's disruptive behavior from derailing said production, and turning this last-ditch effort at career resuscitation into the sort of success that will dazzle his wife and daughter back home. But California is not as he imagined: drought, wildfire, and corporate corruption are omnipresent, and the company behind a mysterious new brand of synthetic water seems to be at the root of it all. Partnering with Cassidy--after having been her reluctant chauffeur for weeks--the two of them investigate the sun-scorched city's darker crevices, where they discover that catastrophe resembles order until the last possible second"--